Penguatan Identitas Bangsa pada Video Teks Proklamasi Bahasa dan Puisi Untuk Sang Redaktur: Kajian Geopolitik - Sholihah*, Husniatin; Arif, Nurul Hamdiyah; Sastrio, Tri Budhi (Universitas Suryakancana, 2025)
This article describes the forms of strengthening national identity in the video text of the Proclamation of Language and the poem For the Editor. Descriptive qualitative was chosen as the method of this research. The data sources in the study were a video containing the text of the Proclamation of Language and a poem entitled For the Editor. Both data sources discuss language and its influence on geographical and political locations so that it is relevant to be analyzed using geopolitical studies. The research data are in the form of words, sentences, and paragraphs related to geography and politics. Data collection was carried out using transcription techniques. The results of the study found three forms of strengthening national identity in the Proclamation of Language text, namely as an international language, unlimited distribution, and a high attitude of mutual cooperation. Meanwhile, in the poem For the Editor, three forms of strengthening national identity were found, namely global cooperation, awareness of historical events, and an invitation to the younger generation.Keywords: geopolitic, language proclamation, poetryABSTRAKArtikel ini mendeskripsikan bentuk-bentuk penguatan identitas bangsa pada video teks Proklamasi Bahasa dan puisi Untuk Sang Redaktur. Kualitatif deskriptif dipilih sebagai metode penelitian ini. Sumber data dalam penelitian adalah video berisi teks Proklamasi Bahasa dan puisi berjudul Untuk Sang Redaktur. Kedua sumber data tersebut membahas tentang bahasa dan pengaruhnya terhadap letak geografi serta politik sehingga relevan dianalisis menggunakan kajian geopolitik. Data penelitian berupa kata, kalimat, dan paragraf yang berkaitan dengan geografi dan politik. Pengumpulan data dilakukan dengan teknik transkripsi catat. Hasil penelitian, ditemukan tiga bentuk penguat identitas bangsa pada teks Proklamasi Bahasa, yakni sebagai bahasa internasional, penyebaran tanpa batasan, dan sikap gotong royong tinggi. Sedangkan pada puisi Untuk Sang Redaktur ditemukan tiga bentuk penguat identitas bangsa yakni kerjasama global, kesadaran peristiwa sejarah, dan ajakan generasi muda. Kata Kunci: geopolitik, proklamasi bahasa, puisi